Review article Variant CJD (vCJD) and Bovine Spongiform Encephalopathy (BSE): 10 and 20 years on: part 2 - Collee, J. Gerald; Bradley, Ray; Liberski, Paweł P. (Folia Neuropathologica, 2006)
Up until February 2006, variant CJD (vCJD), the human disease associated with transmission of BSE from cattle, has been confirmed in 160 patients resident in the UK and 28 elsewhere, some of whom have never visited the UK. Cases have been reported in France (16 cases), Ireland (3), USA (2), Canada, Italy, Japan, the Netherlands, Portugal, Saudi Arabia and Spain (1 each). The presumed main period of hazard for ingestion of the BSE agent in bovine products in the UK is 1984-89, or perhaps up to 1995-6 but at a reduced level. Debated incubation periods for vCJD are discussed, with special reference to the wide, but currently reducing, range of predicted further primary cases in the UK. The primary disease seems to be preferentially acquired by, and expressed in, relatively young people. All but one of the British cases examined so far were homozygous for methionine at the polymorphic codon 129 of the prion protein PRNP gene. Tests of appendix specimens from large numbers of otherwise normal subjects at the time of appendicectomy have revealed lymphoreticular accumulations of PrPSc in a few samples. Furthermore, three patients who died of vCJD had appendices removed by appendicectomy whilst healthy. Two of these appendices were retrospectively shown to be positive for PrPSc and one removed 10 years before clinical onset was negative. This has led to worries regarding the possibility of pre-clinical or sub-clinical prion-associated disease in an unknown proportion of the population. To date, there has been no known association of primary vCJD with occupation, medicines, immunising agents, gelatine, or surgery (including the use of catgut sutures), or exposure to bovine products other than by ingestion. There is much concern that human-to-human (secondary) vCJD infection is transferred by blood transfusion. A possible risk is also perceived from infected blood products, human organs and tissues, or via contaminated surgical instruments or devices though, so far as is known, no cases have yet arisen in this way. Steps have been taken to reduce the risks and much research is in hand in this field. Continued TSE surveillance, the maintenance of adequate preventive controls, attention to possible parenteral challenges, and further research studies are of paramount importance.